2005
DOI: 10.1007/s10812-005-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Surface as a Factor Forming Distinctive Features of Nanodimensional Media

Abstract: 535.853.4 As a result of studying thin-film nano-sized media, it is shown that the extended surface exerts a substantial influence on their distinctive properties. It has been established that, by using special methods to obtain nanosized media under certain conditions, it is possible to form crystal structures with a high concentration of defects of a prescribed type in the near-surface layers of nanocrystals. The correlations found between the conducting and optical properties of thin-film nano-sized stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Studies of LiF films and crystals that have been γ-irradiated under identical conditions have shown that the concentration of color centers is higher in films while more complex color centers are formed more efficiently than in crystals [13,14]. Of course, the surfaces of the films prepared by vacuum sputtering and used in [13,14] are considerably different from the surfaces of ordinary crystals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of LiF films and crystals that have been γ-irradiated under identical conditions have shown that the concentration of color centers is higher in films while more complex color centers are formed more efficiently than in crystals [13,14]. Of course, the surfaces of the films prepared by vacuum sputtering and used in [13,14] are considerably different from the surfaces of ordinary crystals.…”
mentioning
confidence: 99%
“…Of course, the surfaces of the films prepared by vacuum sputtering and used in [13,14] are considerably different from the surfaces of ordinary crystals. Study of the differences in color center formation processes in the near-surface layer and within the volume of the crystal is important because of the prospects for using LiF crystals with color centers for designing components for optoelectronics and integrated optics, and also the need for a deeper understanding of color center formation processes.…”
mentioning
confidence: 99%
“…1 Introduction Because of its importance for basic and applied research [1,2], lithium fluoride (LiF) has been investigated in connection with colour centres (CCs), but very often various authors use crystals grown and coloured by different methods, and the results obtained by them are affected by "technological" impurities [3,4], and crystal bulk and surface defects [3,[5][6][7]. If the colouring is carried out by irradiation with X-or γ-rays, then uniform concentration of CCs throughout the sample is produced.…”
mentioning
confidence: 99%